(untitled) (World Economics and Finance Bulletin, 2025)
The research aimed to measure and analyze the impact of domestic government debt on some indicators of sustainable development in Iraq, represented by (Gross Domestic Product (GDP), government spending on education, and government spending on health). This was done using the ARDL (Autoregressive Distributed Lag) model for both short-term and longterm periods. Semi-annual data for the period (2004-2023) were used, and the research hypothesized that there is both a direct and inverse impact of domestic government debt on some indicators of sustainable development in Iraq. The results of the dynamic interactions in both the short and long term revealed that domestic government debt has both inverse and direct effects on GDP, education spending, and health spending in the short term. In the long term, however, domestic government debt has a direct effect only on GDP and health spending, while it has an inverse effect on education spending. Accordingly, the research recommended that the government diversify funding sources by increasing the issuance of government bonds and attracting foreign investments, while enhancing public debt management to ensure fiscal sustainability. It also suggested strengthening the distributive, service, and mining sectors by improving infrastructure and increasing efficiency, along with improving resource management and directing investments toward projects with high economic and social returns. This would ensure the sustainability of services and promote economic growth in both the short and long term